Phage therapy as an alternative treatment modality for resistant Staphylococcus aureus infections - Atshan, Salman Sahab; Hamat, Rukman Awang; Aljaberi, Musheer A.; Chen, Jung Sheng; Huang, Shih Wei; Lin, Chung Ying; Mullins, Benjamin J.; Kicic, Anthony (MDPI, 2023)
The production and use of antibiotics increased significantly after the Second World War due to their effectiveness against bacterial infections. However, bacterial resistance also emerged and has now become an important global issue. Those most in need are typically high-risk and include individuals who experience burns and other wounds, as well as those with pulmonary infections caused by antibiotic-resistant bacteria, such as Pseudomonas aeruginosa, Acinetobacter sp, and Staphylococci. With investment to develop new antibiotics waning, finding and developing alternative therapeutic strategies to tackle this issue is imperative. One option remerging in popularity is bacteriophage (phage) therapy. This review focuses on Staphylococcus aureus and how it has developed resistance to antibiotics. It also discusses the potential of phage therapy in this setting and its appropriateness in high-risk people, such as those with cystic fibrosis, where it typically forms a biofilm.